Water management in PEMFC - Falcão, D. S. (2010)
The potential of fuel cells for clean and efficient energy conversion is generally recognized. Proton-exchange membrane (PEM) Fuel Cells are among the different types of fuel cells one of the most promising. The water management is a critical problem to overcome in the PEM fuel cell technology. Despite several studies on this topic effective water management is still elusive. Models play an important role in fuel cell development since they enable the understanding of the influence of different parameters on the cell performance allowing a systematic simulation, design and optimization of fuel cells systems. In this work, a model previously developed and validated [1], is used to predict the water transport through the cell. The model takes into account heat and mass transport effects The influence of membrane thickness and transport properties, GDL thickness and structure, reactants pressure and humidification temperatures, on the water content through the membrane and on the cell performance was studied. All these parameters have an important impact in the cell water management. The model predicts the membrane water contents and water concentration profiles along the MEA. This work represents a useful tool to set-up suitable operating conditions and optimized tailored MEAs to produce a better performance of PEM fuel cells.